2017
DOI: 10.1002/ldr.2728
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Ecosystem Functional Enhancement by Forest Restoration: A Meta‐analysis in China

Abstract: Large‐scale forest loss and degradation have dire consequences for biodiversity maintenance and provision of vital ecosystem services. Despite recent increasing efforts for forest restoration and sustainable management, there have been no comparative studies of biological taxonomy and multiple ecosystem functions to assess the effectiveness of forest restoration programmes, and how they vary through space and time. Here, we provided a quantitative assessment of the recovery of biodiversity and ecosystem functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 62 publications
0
34
0
1
Order By: Relevance
“…Our Landsat-based results showed that the forests in northeast China decreased by 1051 km 2 , about 42.04 km 2 y −1 during 1990-2015. Despite this decline, northeast China's forest coverage remains 41 percent of total land area, which is higher than China's average of 21.63% [45] and the world's average of 31% [11]. From the perspective of net change in different periods, forest area in northeast China shifted from net loss during 1990-2000 to net gain during 2000-2015 (Table 3).…”
Section: Forest Dynamics and Potential Drivers In Northeast Chinamentioning
confidence: 99%
See 2 more Smart Citations
“…Our Landsat-based results showed that the forests in northeast China decreased by 1051 km 2 , about 42.04 km 2 y −1 during 1990-2015. Despite this decline, northeast China's forest coverage remains 41 percent of total land area, which is higher than China's average of 21.63% [45] and the world's average of 31% [11]. From the perspective of net change in different periods, forest area in northeast China shifted from net loss during 1990-2000 to net gain during 2000-2015 (Table 3).…”
Section: Forest Dynamics and Potential Drivers In Northeast Chinamentioning
confidence: 99%
“…In the mountainous area of east Jilin Province, Kuang et al found that forest changes mainly took place in the area with elevation of 300-900 m and slope between 0-11 • during the period 1954-2000 [48]. An estimated two billion ha of forests is degraded worldwide [49], which is largely induced by agricultural expansion and urban sprawl [11,50,51]. It is preferable for cropland to be located in low elevations and on small slopes, for example, 67.4% of the cropland in China was distributed in the area of elevation less than 500 m [52].…”
Section: Forest Dynamics and Potential Drivers In Northeast Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Croplands on slopes greater than 25° were abandoned, and vegetative succession allowed to proceed naturally from nonwoody plants to woody shrubs and ultimately to mature secondary forest, with the ultimate objective of ecosystem restoration to conditions similar to pristine primary forest (Xu, Yin, Li, & Liu, ). The regeneration of plant communities under GGP in degraded karst landscapes has been largely successful, indicated by increased NPP and soil organic matter (SOM) stocks, and the stabilization of soil profiles by vegetative canopy cover and roots that moderate further loss by erosion (Chang et al, ; Ren, Lu, Fu, & Zhang, ; Tong et al, ). SOM contains soil organic carbon (C) and nutrients (including nitrogen [N] and phosphorus [P]) and is recognized as a key indicator of soil health and productivity in agricultural systems (Dungait et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Decision making as well as timely and adequate interventions in complex systems require indicators for tracking the states of a system. The environmental rehabilitation of mining areas, which is intended to restitute ecosystems and their functionality to as close as possible to premining levels to reduce the overall impacts of mining operations (Perring et al, 2013), is affected by a myriad of forces operating at multiple spatiotemporal scales (Arroyo-Rodríguez et al, 2017;Ren et al, 2017). The monitoring of rehabilitation success and the definition of effective indicators of rehabilitation status are necessary for monitoring whether rehabilitation goals are achieved (Gastauer et al, 2018a;Latawiec and Agol, 2016).…”
Section: Introductionmentioning
confidence: 99%